Proteins Concepts in Biochemistry - Paulo Almeida (Garland Science, 2016)
Proteins: Concepts in Biochemistry teaches the biochemical concepts underlying protein structure, evolution, stability, folding, and enzyme kinetics, and explains how interactions in macromolecular structures determine protein function. Intended for a one-semester course in biochemistry or biophysical chemistry with a focus on proteins, this textbook emphasizes the logic underlying biophysical chemical principles. Problems throughout the book encourage statistical and quantitative thinking. The text is ideal for senior undergraduates, first year graduate students, and practitioners in chemistry, biochemistry, biology, and biophysics.